HLA Diversity in Saudi Population: High Frequency of Homozygous HLA Alleles and Haplotypes - Chentoufi, Aziz Alami; Uyar, F. Aytül; Chentoufi, Hiba A.; Alzahrani, Khalid; Paz, Maria; Bahnassy, Ahmed; Elyamany, Ghaleb; Elghazaly, Assem (Frontiers in Genetics, 2022)
Human leukocyte antigens (HLA) diversity has a tremendous impact on shaping the transplantation practices, transfusion-associated graft versus host disease prevention strategies, and host–pathogen interactions. Here, we conducted a retrospective study of HLA class I and class II homozygosity at allelic and haplotype levels in unrelated individuals genotyped from 2012 to 2016 in a tertiary hospital in the capital of Saudi Arabia. Among 5,000 individuals, 2,773 individuals meet inclusion criteria and were retrospectively analyzed for HLA-A, -B, -C–DRB1, and -DQB1 homozygosity at allelic and haplotype levels. HLA molecular typing was performed using a commercial reverse sequence-specific oligonucleotide (rSSO) kit. We were able to identify 15 HLA-A, 20 HLA-B, 11 HLA-C, 13 HLA-DRB1, and five HLA-DQB1 homozygous alleles demonstrating a very low genetic diversity in the Saudi population. The highest homozygosity in HLA class I was found in locus C followed by A and B (20.3% > 16.1% > 15.5%; p < 0.001) where the most homozygote alleles were A*02 (9.2%), B*51 and B*50 (5.7% and 3.7%), and C*07, C*06, and C*15 (7.2%, 5.48%, and 3.3%) and in HLA class II, the highest homozygosity was found in locus DQB1 compared to DRB1 (31.71% > 19.2%; p < 0.001), with the most common homozygote alleles being DRB1*07 and DRB1*04 (5.33% and 4.2%) and DQB1*02, DQB1*06, and DQB1*03 (13.55%, 7.92%, and 7.64%). The frequency of finding an individual with one homozygote allele was (24.6%), two homozygote alleles (13.5%), three homozygote alleles (4.7%), four homozygote alleles (3.4%), and five alleles were (4.8%). The most frequent homozygote haplotypes are A*23∼C*06∼B*50∼DRB1*07∼DQB1*02 and A*02∼C*06∼B*50∼DRB1*07∼DQB1*02. This study shows low diversity of both class I and II alleles and haplotypes in the Saudi population, which would have a significant impact on shaping the transplantation practices, transfusion-associated graft versus host disease prevention strategies, and host–pathogen interactions.